Comparative structure analyses of cystine knot-containing molecules with eight aminoacyl ring including glycoprotein hormones (GPH) alpha and beta subunits and GPH-related A2 (GPA2) and B5 (GPB5) molecules - Combarnous Yves; Cahoreau Claire; Alvarez Eva (BMC, 2009)
Abstract Background Cystine-knot (cys-knot) structure is found in a rather large number of secreted proteins and glycoproteins belonging to the TGFbeta and glycoprotein hormone (GPH) superfamilies, many of which are involved in endocrine control of reproduction. In these molecules, the cys-knot is formed by a disulfide (SS) bridge penetrating a ring formed by 8, 9 or 10 amino-acid residues among which four are cysteine residues forming two SS bridges. The glycoprotein hormones Follicle-Stimulating Hormone (FSH), Luteinizing Hormone (LH), Thyroid-Stimulating Hormone (TSH) and Chorionic Gonadotropin (CG) are heterodimers consisting of non-covalently associated alpha and beta subunits that possess cys-knots with 8-amino-acyl (8aa) rings. In order to get better insight in the structural evolution of glycoprotein hormones, we examined the number and organization of SS bridges in the sequences of human 8-aa-ring cys-knot proteins having 7 (gremlins), 9 (cerberus, DAN), 10 (GPA2, GPB5, GPHα) and 12 (GPHβ) cysteine residues in their sequence. Discussion The comparison indicated that the common GPH-alpha subunit exhibits a SS bridge organization ressembling that of DAN and GPA2 but possesses a unique bridge linking an additional cysteine inside the ring to the most N-terminal cysteine residue. The specific GPHbeta subunits also exhibit a SS bridge organization close to that of DAN but it has two additional C-terminal cysteine residues which are involved in the formation of the "seat belt" fastened by a SS "buckle" that ensures the stability of the heterodimeric structure of GPHs. GPA2 and GPB5 exhibit no cys residue potentially involved in interchain SS bridge and GPB5 does not possess a sequence homologous to that of the seatbelt in GPH β-subunits. GPA2 and GPB5 are thus not expected to form a stable heterodimer at low concentration in circulation. Summary The 8-aa cys-knot proteins GPA2 and GPB5 are expected to form a heterodimer only at concentrations above 0.1 microM: this would be consistent with a short-term paracrine role but not with an endocrine role after dilution in circulation. Consequently, GPA2 and GPB5 could exert separate endocrine roles either during development and/or during adult life of both vertebrates and invertebrates.